Autosomal dominant tubulointerstitial kidney diseases (ADTKD) - Knaup, Karl; Wiesener, M. S. (Nephrologe, 2019)
Hereditary kidney diseases, particularly those with onset in adulthood, are underdiagnosed due to various reasons, with the exception of autosomal dominant polycystic kidney disease (ADPKD). Among these the autosomal dominant tubulointerstitial kidney diseases (ADTKD) form the largest heterogeneous group of hereditary diseases in adulthood. In cases of negative or unknown family history and a frequently not carried out kidney biopsy, which additionally often only achieves an insufficient differentiation between ADTKD and other potential disease entities, only a molecular genetic analysis leads to a clear classification of the disease. This article describes the clinical phenotype of ADTKD, the subtypes with the so far identified causal heterozygous mutations in 5 candidate genes, as well as the possible differential diagnoses and pathomechanisms. In addition, the already existing treatment approaches for delaying the progression of renal insufficiency are presented. The future necessary measures and results of clinical and also basic research, which could lead the way to specific and therefore more effective treatment interventions are discussed.
CRIS-Team WoS Importer:2019-03-15